The evil witch in the Malaysian fairy tale: the bifurcated representations of Rosmah Mansor post the 1MDB scandal - Selvarajan, Tamyra (2025)
Rosmah Mansor, a well-known Malaysian figure, has received scathing criticism. During her tenure as First Lady, she was engaged in numerous scandals, most notably the 1MDB financial crisis. This study looks at negative memes about Rosmah and how she keeps up her public persona despite her tarnished reputation and fall from grace as Malaysia's First Lady. It also looks at how she disturbs public opinion despite these things, which can be seen as a challenge to her authority. This study use memes as a cultural text. The six memes share two motifs: they criticise Rosmah's appearance and domineering demeanour, which appeared most frequently in the identified memes. The term "pop polyvocality" (Milner, 2013) was used to investigate the chosen memes due to their pop culture references. This strategy can be regarded as a dissident challenge to Rosmah and the corrupt political systems that maintain her power. The following research examines how Rosmah Mansor's Minangkabau ethnicity adds to her long-term presence, irrespective of her fall from grace. She raises ethical questions by presenting herself as a Minangkabau woman rather than a Muslimah woman, challenging the concept that Islam is the sole component of Malay identity, and she uses case studies from Minangkabau forums and news reports. According to the study's findings, her high-profile and agentic behaviour continue to generate public concern. As a result, despite the public's poor perception of her, particularly online, her influence remains powerful. The memes can also be seen as a form of resistance to this influence. Naturally, Minangkabau research has few prospects, but the challenges of this study may provide case studies and an interdisciplinary approach that integrates media studies and anthropological research to bring new advancements to the field.